Defect‐Driven Interfacial Electronic Structures at an Organic/Metal‐Oxide Semiconductor Heterojunction. (15th May 2014) - Winget, Paul; Schirra, Laura K.; Cornil, David; Li, Hong; Coropceanu, Veaceslav; Ndione, Paul F.; Sigdel, Ajaya K.; Ginley, David S.; Berry, Joseph J.; Shim, Jaewon; Kim, Hyungchui; Kippelen, Bernard; et al.
<x xml:space="preserve">Abstract</x> The electronic structure of the hybrid interface between ZnO and the prototypical organic semiconductor PTCDI is investigated via a combination of ultraviolet and X‐ray photoelectron spectroscopy (UPS/XPS) and density functional theory (DFT) calculations. The interfacial electronic interactions lead to a large interface dipole due to substantial charge transfer from ZnO to 3, 4, 9, 10‐perylenetetracarboxylicdiimide (PTCDI), which can be properly described only when accounting for surface defects that confer ZnO its n‐type properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>